2005
DOI: 10.1038/nature04029
|View full text |Cite
|
Sign up to set email alerts
|

Human subtelomeres are hot spots of interchromosomal recombination and segmental duplication

Abstract: Human subtelomeres are polymorphic patchworks of inter-chromosomal segmental duplications at the ends of chromosomes. We provide evidence here that these patchworks arose recently through repeated translocations between chromosome ends. We assess the relative contribution of the major modes of ectopic DNA repair to the formation of subtelomeric duplications and find that nonhomologous end-joining predominates. Once subtelomeric duplications arise, they are prone to homology-based sequence transfers as evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
424
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(450 citation statements)
references
References 47 publications
17
424
3
6
Order By: Relevance
“…Interestingly, the subtelomeric gene duplication rate is significantly higher than the genome average. Thus, the authors conclude that this is both advantageous for evolution and may also have pathological consequences [Linardopoulou et al, 2005]. In the context of our discussion, we emphasize that telomeres and subtelomeric sequences are hot spots of evolution and genomic instability.…”
Section: Telomeres and Evolutionmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, the subtelomeric gene duplication rate is significantly higher than the genome average. Thus, the authors conclude that this is both advantageous for evolution and may also have pathological consequences [Linardopoulou et al, 2005]. In the context of our discussion, we emphasize that telomeres and subtelomeric sequences are hot spots of evolution and genomic instability.…”
Section: Telomeres and Evolutionmentioning
confidence: 64%
“…It has been reported that human subtelomeric sequences are recombination and duplication hot spots [Linardopoulou et al, 2005]. Subtelomeric sequences are involved in interchromosomal recombinations and segmental duplications.…”
Section: Telomeres and Evolutionmentioning
confidence: 99%
“…One possibility is that GRCh38 does not well represent the sequence of chr4 in this region. The other possible reason is chromosomal translocation between chr4 and chr10, which is known to be frequent [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Because reports conflict on the gene content of LCRs [20,21,[67][68][69][70], depending on methodology, species and the quality of the data, it is not clear to what extent LCRs have a role in the duplication of entire genes. However, there is substantial evidence that LCRs contain fragments of coding sequence and are likely to be the sites of new gene formation by domain shuffling.…”
Section: Temporal Analysismentioning
confidence: 99%
“…In studies of recent duplications, sequence analysis has also been used to diagnose the genomic mechanisms that drive various duplication processes [20,21]. Evidence of transposition can be found in the characteristic sequence patterns associated with known families of TEs and their integration sites.…”
Section: Introductionmentioning
confidence: 99%